Seismic vulnerability and the loss of the traditional adobe buildings in Jojutla, Morelos, México, after the 2017 earthquake - Sánchez Calvillo, Adrià (Centro Universitario de Arte, Arquitectura y Diseño, 2021)
Adobe dwellings are the most representative constructive typologies of the traditional architecture and local culture of Mexico. In the last decades these systems have been abandoned and displaced by modern materials and techniques, a situation enhanced by the recent seismic events, especially the ones which struck the country in 2017. The city of Jojutla, in the State of Morelos, was one of the most affected by the 2017 Puebla earthquake, suffering several damages of the built heritage, highlighting the adobe dwellings in the historic centre. The following paper presents the research carried in the city of Jojutla regarding the seis- mic impact over the earthen constructions of the region after the 2017 earthquake. There was applied a research methodology which included techniques like geographic information systems, characterisation of the earthen construction materials in the laboratory, and the analysis and revision of the local building codes and risk management plans. There could be noticed several structural de- ciencies in the dwellings of the town, as well as wrong urban planning and risk management plans, contributing to increase the seismic vulnerability of the constructions. On the basis of pre- vious research and the results presented, it could be established that the lack of protection and exposition of the adobe dwellings, in combination with the oblivion of the traditional techniques and bad practices, caused the complete demise of this constructive culture in the studied region.